Struktur Komunitas Nekton di Danau Pondok Lapan Desa Naman Jahe Kecamatan Salapian Kabupaten Langkat (Community Structure of Nekton in Pondok Lapan Lake’s Desa Naman Jahe Kecamatan Salapian Kabupaten Langkat North Sumatera) - Nurul Azmi; Yunasfi Djayus; Ahmad Muhtadi (AQUACOASTMARINE, 2015)
Nekton is organism that can swim and move on their own accord with exampleamphibians and aquatic insect. This study aims to determine the structure of nektoncommunity and relation about physical and chemical conditions in the Lake Pondok Lapan .This study was carried out from January to March 2015. Data collection were nekton speciescomposition and abundance, as well as water quality data as a supporter. Nekton retrievalused fish nett and fishing rod. The results showed there were 5 of the Ordo, of which 4 ordobelongs to fish and 1 ordo of shrimp. Sepat rawa (Trichogaster trichopterus) was found to becaught at most in the amount of 141 and 56% relative abundance. Diversity nekton in PondokLapan lake including low at 1,95. General dominance index value approaching 0 is equal to0,23. It shows that almost no one species dominates. Value uniformity tends to 1. The figureshows the number of individuals of each type of deployment is the same. Pearson correlationanalysis results showed that temperature, depth, water transparancy, pH ,DO and COD has apositive correlation with the abundance of nekton while turbidity and COD have a negativecorrelation or do not have the relationship with the abundance of nekton.Keywords: Pondok Lapan Lake, Structure Comunity, Nekton.